Design principles for engineering ionic liquid-gold nanoparticles for therapeutic delivery to the brain - Shmool,TA; Martin,LK; Jirkas,A; Morse,SV; Contini,C; Elani,Y; Hallett,JP (ACS Nano, 2025)
Ionic liquid (IL) nanotechnology holds significant promise for designing nanoscale materials with tunable viscosity, polarity, and thermal stability for advanced therapeutic applications. However, the field currently lacks comprehensive guidelines for integrating ILs into complex therapeutic formulations. Herein, we propose the key design considerations for engineering immunoglobulin G (IgG) conjugated to gold nanoparticles (AuNPs) in the presence of choline-based ILs. By judicious IL cation and anion selection, we fine-tune the supramolecular assemblies and leverage the unique physicochemical properties of ILs to impart AuNPs with advantageous characteristics including enhanced structural, thermal, and thermodynamic stabilities, highly tunable morphologies, and markedly reduced aggregation propensities. Through systematic circular dichroism measurements, the thermodynamic parameters of the complex formulations were determined, offering insight into the IgG conformational changes and design parameters for systems of enhanced IgG conjugation to AuNP surfaces. In demonstrating the power of our design approach, the complex formulation of IgG-choline chloride-AuNPs, also including trehalose, histidine, and arginine, was delivered via focused ultrasound and microbubbles across the blood–brain barrier and showed a 7.6-fold increase in delivery in vivo compared to the traditional formulation. We demonstrate that IgG-IL-AuNPs can be easily and precisely manipulated at the nanometer scale, enabling the formation of versatile structural configurations. Holistically, we believe the rational design approach developed will advance the engineering of tailored IL-nanocarriers for targeted therapeutic delivery and broaden the scope of IL applications in biomedicine.